Characterization of nuclear microsatellites in Marchantia polymorpha (liverwort) with additional trans-specific analyses - Nicole Rodriguez Ortiz; Niharika Sharma; Tian-Xiong Zheng; James J. Campanella (BioTechniques)
Microsatellites are present in mitochondria, chloroplast, and nuclear DNA, but nuclear microsatellites are more useful genetic tools than those in plastids or mitochondria. Plastid and mitochondrial microsatellites have been identified in the model plant Marchantia polymorpha (liverwort), but no laboratory has published information on nuclear microsatellite loci. The aim of this study was to detect novel nuclear markers in the most commonly employed liverwort species, design PCR primers that would allow amplification, and characterize the subsequently generated loci. We detected 18 polymorphic nuclear loci in M. polymorpha, amplifiable by PCR across all chromosomes. Additionally, trans-specific amplification of the eighteen loci was characterized in the closely related taxa Marchantia emarginata and Marchantia paleacea. All loci were present in M. paleacea, whereas 17 of 18 primer pairs were amplified in M. emarginata.